2023
DOI: 10.3389/fenvs.2023.1138876
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of R&D spending, transport infrastructure development and CO2 emissions in China

Abstract: Over the past few decades, the transportation sector has been the largest contributor to CO2 emissions in China. Research and Development spending leads to technological innovation in the country and could affect the CO2 emission in the country. Therefore, this study analyzes the nexus between CO2 emissions, transport infrastructure and R&D spending in China. A QARDL approach was used for the data analysis, which revealed Research and Development and Transport infrastructure has a positive impact on CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Similarly, RD spending is anticipated to decrease the reliance of EMEs on fossil fuels, encourage the adoption of renewable energy, and increase investment in ETs. Our findings are in line with the justifications of the studies by Kihombo et al (2021), Petrović and Lobanov (2020b), Han et al (2023) and Herzer (2022), who argued that RD investment positively contributes to CO2 mitigation and thus contributes to GEG.…”
Section: The Effects Of Rd Ets and Fg On Green Growthsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, RD spending is anticipated to decrease the reliance of EMEs on fossil fuels, encourage the adoption of renewable energy, and increase investment in ETs. Our findings are in line with the justifications of the studies by Kihombo et al (2021), Petrović and Lobanov (2020b), Han et al (2023) and Herzer (2022), who argued that RD investment positively contributes to CO2 mitigation and thus contributes to GEG.…”
Section: The Effects Of Rd Ets and Fg On Green Growthsupporting
confidence: 92%
“…Additionally, Petrovi and Lobanov (2020a) revealed that an increase in RD investments reduces CO 2 emissions over time. Similarly, Han et al (2023) proved that accelerating RD reduces CO 2 emissions only at lower quantiles. Nonetheless, Pata et al (2023) asserted that sustainable energyrelated RD reduces CO 2 emissions, while nuclear energy-related RD has little or no effect on the quality of the environment.…”
Section: Empirical Literature and Hypothesis Development 221 Environm...mentioning
confidence: 90%
See 1 more Smart Citation
“…As for the influencing factors of UGSD, existing literature mainly explored the impact of FDI (Gao et al, 2022;Xu et al, 2022), economic agglomeration (Hao et al, 2022), environmental regulation (Feng et al, 2021), and technological progress (Sun et al, 2022) on UGSD. Additionally, the technological innovation and information level would also effectively promote urban governance and service efficiency besides the energy element and release their supporting role for UGSD (Xu et al, 2021;Han et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, R&D as one of the crucial determinants of environmental quality is less explored in the literature. However, R&D is closely linked with environmental quality (Han et al, 2023). Expanding R&D activities triggers technological innovation in the energy sector and improves energy efficiency.…”
Section: Introductionmentioning
confidence: 99%